ENHANCEMENT OF SOLUBILITY AND DISSOLUTION RATE OF ACETYLSALICYLIC ACID VIA CO-CRYSTALLIZATION TECHNIQUE: A NOVEL ASA-VALINE COCRYSTAL - H. K., SHANTHALA; H. V., JAYAPRAKASH; RADHAKRISHNA, MUNIGANTI; B. H., JASWANTH GOWDA; PAUL, KARTHIKA; SHANKAR, S. J.; AHMED, MOHAMMED GULZAR; A., SANJANA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aims to synthesize acetylsalicylic acid (ASA) cocrystals using valine as a coformer via a co-crystallization technique to increase the solubility and dissolution rate of ASA. Methods: The ASA-valine cocrystal (1:1 molar ratio) was prepared using the solvent evaporation technique with ethanol: water (50:50). The cocrystal was characterized using Fourier transform infrared spectroscopy (FT-IR), Differential scanning calorimetry (DSC), Powder X-ray diffraction (PXRD), Scanning electron microscopy (SEM), melting point to confirm the formation of cocrystal. The evaluation of cocrystal was done by drug content determination, solubility and dissolution studies. Results: The prepared cocrystal was successfully confirmed for the formation of a hydrogen bond. The melting point of prepared cocrystal was decreased compared to pure ASA and valine, which indicated the formation of a new crystalline form. The FT-IR studies showed the formation of a new hydrogen bond by shifting the-O-H,-C=O and-N-H functional groups. SEM studies ensured that the prepared cocrystals were in needle-like appearance. Finally, DSC and PXRD studies were also indicated the successful formation of ASA-valine cocrystal. The drug release of cocrystal was found to be 100% at 60th min. Where in the case of pure ASA and marketed product of ASA exhibited the dissolution rate of 59% and 69% at 60th min respectively. Conclusion: The co-crystallization technique can be adopted as the best strategy to increase the solubility and dissolution rate of BCS class 2 drugs. Therefore the prepared ASA-valine cocrystal can be a greater alternative to increase the solubility and dissolution rate compared with pure and marketed ASA.